3D Nanostructures for Tissue Engineering, Cancer Therapy, and Gene Delivery. (1st December 2020) - Gholami, Ahmad; Hashemi, Seyyed Alireza; Yousefi, Khadije; Mousavi, Seyyed Mojtaba; Chiang, Wei-Hung; Ramakrishna, Seeram; Mazraedoost, Sargol; Alizadeh, Ali; Omidifar, Navid; Behbudi, Gity; Babapoor, Aziz
Abstract : The self-assembling is a spontaneous progression through which objects of nanophase/molecules materialize into prepared collections. Several biomolecules can interact and assemble into highly structured supramolecular structures, for instance, proteins and peptides, with fibrous scaffolds, helical ribbons, and many other functionalities. Various self-assembly systems have been established, from copolymers in blocks to three-dimensional (3D) cell culture scaffolds. Another advantage of self-assembly is its ability to manage a large variety of materials, including metals, oxides, inorganic salts, polymers, semiconductors, and various organic semiconductors. The most basic self-assembly of 3D nanomaterials is three primary forms of nanostructured carbon-based materials that perform a critical role in the progress of modern nanotechnologies, such as carbon nanotubes (CNTs), graphene, and fullerene. This review summarized important information on the 3D self-assembly nanostructure, such as peptide hydrogel, graphene, carbon nanotubes (CNTs), and fullerene for application in gene delivery, cancer therapy, and tissue engineering.